KENALI DIRI DAN KELUARGA TENTANG STROKE DENGAN LANGKAH “CERDIK” - Arabta Malem Peraten Pelawi; Roulita; Kiki Deniati; Nutri Yunika K Gea; Ernauli Meliyana; Lisna Agustina; Lisna Nuryanti (Rena Cipta Mandiri, 2024)
Stroke is defined as a clinical manifestation of impaired cerebral function, either focal or generalized (global), which occurs rapidly, lasts more than 24 hours, or ends in death, without any cause other than vascular disorders being found. Stroke is the third leading cause of death after heart disease and cancer in the United States. The prevalence in America in 2005 was 2.6%. The prevalence increases according to age group, namely 0.8% at age 18-44 years, 2.7% 5 at age 45-64 years and 8.1% at age 65 years or older. Men and women have a prevalence that is not much different, namely men 2.7% and women 2.5%. The aim is to improve society regarding stroke, stroke prevention and healthy living. The research results showed that there were differences before and after health analysis results using paired sample t-test with the results of P value (0.037) < alpha (0.05). It can be concluded that there is an influence after health education has been carried out on public knowledge about stroke.